Trajetória ocupacional e sofrimento psíquico de mulheres trabalhadoras motoristas de aplicativo - Caravita, Marina Victorelli (Universidade Federal de São Carlos, 2025)
Uberization produces a new form of mediation of the subordination of workers who take responsibility for the main means of production. The creation of transport apps has contributed to the growth of the occupation, also causing a redefinition of the image of the driver, previously associated with the male gender. However, female app drivers still face inequalities. The aim of this study was to understand the occupational trajectory of female drivers of private transportation by app. This is a qualitative, exploratory, cross-sectional study based on semi-structured interviews with four female app drivers, two cooperative and two non-cooperative. The interviews were audio-recorded and transcribed in full. The research protocol was approved by UFSCar’s CEP (CAAE No. 77876024.6.0000.5504). The data was analyzed using thematic analysis, allowing the main dimensions of the participants’ work experience to be identified. Among the main findings were the precariousness of the work of app drivers, the emotional overload resulting from insecurity and long working hours, and the perception of autonomy as an ambivalent element, which simultaneously represents flexibility and financial instability. It was also observed that, in the case of female cooperative drivers, the cooperative plays a significant role in reducing the psychological burden, providing emotional support and fairer working conditions. However, gender inequality remains a structural challenge, influencing both work dynamics and the safety of female drivers. Thus, the results suggest the need for public policies and collective strategies to mitigate the negative impacts of uberization and promote greater equity in the app-based transport sector.
Occupational trajectory and psychological distress of female app drivers
Keywords: Trabalho; Gênero; Cooperativismo; Sofrimento; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::PAPEIS E ESTRUTURAS SOCIAIS; INDIVIDUO